Strategy for Developing Vegetable Commoditiies Based on Urban Farming - Fahmi, Ainul Wahdania; Dwi Hastuti, Diah Retno; Kamaruddin, Citra Ayni; Abd. Rahim; Sri Astuty (JURNAL AGRIBISAINS, 2025)
The rapid growth of urban populations in Makassar City poses significant challenges to agricultural land availability and food security. Urban farming offers an innovative solution by utilizing limited spaces for vegetable cultivation. This study aims to formulate strategies for developing vegetable commodities based on urban farming by identifying internal and external factors and determining strategic priorities. A quantitative approach was employed, with data collected through questionnaires, interviews, observations, and documentation. SWOT analysis was applied to map strengths, weaknesses, opportunities, and threats, while the Analytical Hierarchy Process (AHP) was used to determine the main strategies. The findings reveal that urban farming development is positioned in an aggressive quadrant (quadrant I), indicating that internal strengths can be optimized to seize external opportunities. The priority strategies include leveraging the strategic locations of women farmer groups (KWT) to enhance distribution and marketing of harvests, both directly and through digital platforms, and optimizing production facilities and government support to improve vegetable quality and quantity. This study concludes that developing vegetable commodities through urban farming in Makassar City has high potential to strengthen food security and improve community welfare.